ANALISIS PENDAPATAN PADA USAHA INDUSTRI TAHU MITRA CEMANGI DI KOTA PALU - Rondonuwu, Aldri; Sulaeman, Sulaeman (AGROTEKBIS, 2018)
One of the agricultural commodities with great potential in the agro-industrial sector is soybean. It is one of the important food crops in the context of national food security. The soybean processing industry is expected to increase its economic value and revenue. This study aimwas to determine the rate of income earned by Tofu Industry of CemangiPartner in Palu city. The tofu industry was located in Boyaoge village Tatanga sub district of Palu city.The research respondents are purposively determined consisting of the owner of the tofu industry and its two employees.Primary data collected was obtained by direct observation and interviews with therespondentsusing a list of questions (questionaire). Secondary data were obtained from authorities and literature relevant with the aim of this study. The data was analyzed using the analysis of income. The tofu industry was found of being capable to generate revenue IDR.21,989,129.23/month during the period of September to October 2016.